Activating Classroom Interaction through Think–Pair–Share: Evidence from Chemistry Learning - Roswati, Roswati; Wahyuni, Iin; Afriani, Romi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to improve the chemistry learning outcomes of class X students at the Muallimin Muhammadiyah Bangkinang Islamic Boarding School on the main material of electrolyte and non-electrolyte solutions through the application of the Think Pair Share type cooperative learning model. Methodology: The subjects of this research were 10th grade students of the Muallimin Muhammadiyah Bangkinang Islamic Boarding School. The number of students was 24 students consisting of 10 male students and 14 female students. The stages passed in the classroom action research were: 1) Planning/preparation of action, 2) Implementation of action, 3) Observation, and 4) Reflection. Main Findings: Based on the analysis of research results and discussion, it was concluded that the application of the Think Pair Share type of cooperative learning model can improve the chemistry learning outcomes of class X students of the Muallimin Muhammadiyah Bangkinang Islamic Boarding School. This is illustrated by the results of the learning completion obtained by students in accordance with the learning completion requirements set in the class. Student learning outcomes have met the minimum completion criteria as determined, where out of 24 students, 20 students have completed the learning, or are above the classical completion (75%). Novelty/Originality of this study: The novelty of this study is to determine the effectiveness of applying the think pair share type cooperative learning model to improve chemistry learning outcomes in the discussion of electrolyte and non-electrolyte solutions.